Seahorse (Hippocampus sp): opportunities in assisted reproduction with nanotechnology approach - Trisnawati Mundijo; Yurnadi Hanafi Midoen; Radiana Dhewayani Antarianto (Konsorsium Ilmu Biomedik Indonesia (KIBI), 2021)
Seahorse (Hippocampus sp) is the unique fish, because the male is pregnancy. The seahorse not only given an economic value but also have a potential drug for medical use, which is have a steroid an aphrodisiac for fertility. The previous studies have reported the function seahorse extract and have been studied both in vitro and in vivo to know the effects from the natural product. Nowadays, infertility caused many factors, such as a factor from the male including spermatogenesis and testis disorder. In decade, there is the treatment for infertility used GnRH therapy, but it still controversy between the impact in reproductive system and needed the study. GnRH in vertebrate has a G receptor from kisspeptin gene to transcription promote and suggested a key regulator reproductive with a kiss 1 gene, which is the same function in mammals and fishes. In this condition, it is suggested a bioactive compound in seahorse can be investigated to replace a treatment infertility in male with GnRH therapy. It can be done through drug delivery systems with several carrier systems, such as nanoparticles. In the future, bioactive compound from seahorse needed the study to explore a potential drug in medical use including the efficiency and efficacy for fertility in human with nanotechnology approach.